(untitled) (Sains Humanika, 2015)
Criticism of Shariah courts is no longer regarded as a new issue. Given that the majority of clients in the Shariah Courts are women, causes the issue of discriminationÂ affecting women in the administration of the Shariah Court itself. This study will identify some critical issues regarding gender bias which occurred in the Shariah Court. The method used in this research is the study of literature by examineÂ several mediums such as the Quran, books, Enactment Act, newspapers, and web sites of certain organizations related to the issue of gender bias. The study found that women-related issues that arise in the Shariah Court is not true and sometimes is seen as a bit excessive while the allocated Shariah Court jurisdiction was doing its best. However, as a professional body, the Shariah Court should accept criticism from the positive side and to strive harder towards improving a better system administration.